Capturing health literacy assessment in the electronic health record through evidence-based concept creation: A review of the literature and recommendations for action. (September 2019) - Wetta, Ruth E; Severin, Roberta D; Gruhler, Heidi; Lewis, Nate
Health literacy is the capacity to understand and act upon health-related information and navigate the healthcare system. Published evidence demonstrates a relationship between health literacy and health status. Because of this, there are increasingly calls for a health literacy assessment to be collected and stored in the electronic health record for use by the healthcare team. This article describes the results of a literature review of health literacy assessment instruments with the goal of formulating semantically interoperable concepts that may be used to store the interpretation of the health literacy assessment in the electronic health record. The majority of health literacy instruments could be stored in the electronic health record using a three-concept solution of inadequate, marginal and adequate health literacy. This three-concept solution fully supports semantic interoperability needs across the patient care spectrum.